Microleakage Evaluation of Two Methacrylate-Based Composites (GC Kalore and Luna SDI) in Class II Restorations: A Laboratory Study - Kooshan Moradi; Sadaf Sadat Mahmoudinezhad; Mehran Mapar (International Journal of Biomaterials)
Objective. In recent years, dental composite resins such as tooth-colored restoration are frequently used to restore dental cavities, coronal fractures, and congenital defects. This study aimed to evaluate the microleakage of two methacrylate-based composites (GC Kalore and Luna SDI) in class II restorations. Materials and Methods. In this experimental study, a total of 18 intact human premolars previously extracted for periodontal and orthodontic reasons were randomly divided into two groups. Similar class II cavities (box only) were prepared on all teeth and restored with two different composites. In group 1, a bonding agent (Single Bond 2-SB2; 3M ESPE) and Luna SDI composite in mesial cavities and GC Kalore composite in distal cavities were used. In group 2, Single Bond 2 and GC Kalore composite in mesial cavities and Luna SDI composite in distal cavities were applied. They were then subjected to 2000 thermal cycles in a water bath between 5–55°C (dwell time: 30 seconds in every bath and transfer time: 10 seconds). Then, they were immersed in a 2% basic fuchsin dye solution for 24 hours. After rinsing with water, they were sectioned mesiodistally and evaluated for microleakage using a stereomicroscope. Results. Independent t-test (Mann–Whitney test) showed no statistically significant difference for microleakage in mesial and distal class II restorations between GC Kalore composite and Luna SDI composite (p = 1.000) (p= 0.852). A total of 83.4% of the Luna SDI composite samples and 66.6% of the GC Kalore composite had a microleakage score of ≤3 in class II cavities. Conclusion. In the present study, marginal microleakage was found mainly at the gingival floor extending to 1/3 of the axial wall for the Luna SDI composite and GC Kalore composite. Furthermore, no statistically significant difference was found between the microleakage of the Class II cavities restored with Luna SDI composite and GC Kalore composite.